PENGARUH KEMATANGAN BUAH KELAPA SAWIT VARIETAS DXP BAH LIAS TERHADAP KADAR MINYAK SAWIT MENTAH (CPO) - Feny Rahmadhania; Pardamenta Sembiring; Marshal Arifin Sinaga (Jurnal Agro Estate, 2019)
One of the successes of processing at the Palm Oil Mill (POM) is the quality of the raw material for Fresh Fruit Bunches (FFB). The degree of maturity of FFB at harvest is related closely to CPO oil content and free fatty acid content (FFA). One of the varieties grown on oil palm plantations is the DxP Bah Lias variety produced by Bah Lias Research Station (BLRS). The study was conducted in April - June 2017 at the Laboratory of PT. Betami in Kuala Simpang, Aceh Tamiang. FFB samples were obtained from Division I of the Rantau Garden PT. Betami. The study aims to determine the effect of maturity fraction of oil palm FFB on the levels of CPO. The fractions studied were 0, 1, 2, 3, and 4 fractions. The results showed that the highest CPO yield was fraction 3, 26.1% and the lowest fraction 0 with a yield of 22%.